Optimized protocols for generating half-sized embryos from separated first two blastomeres in green sea urchin and Xenopus laevis - Orlov, Eugeny E.; Timoshina, Polina S.; Parshina, Elena A.; Eroshkin, Fedor M.; Bannikova, Maria A.; Zaraisky, Andrey G. (Frontiers in Cell and Developmental Biology, 2025)
The ability to restore normal body proportions after size reduction is a remarkable feature of early development. At the dawn of experimental embryology, Hans Driesch demonstrated that separated sea urchin blastomeres can develop into fully proportioned organisms, revealing an intrinsic capacity for embryonic scaling. However, the molecular mechanisms that enable this phenomenon remain poorly understood. Modern investigations of scaling, particularly those relying on bulk omics approaches, require reliable methods for producing large numbers of embryos that differ in size from wild-type embryos. Here, we present optimized protocols for generating half-sized embryos from separated blastomeres in two phylogenetically distant model organisms: the green sea urchin (Strongylocentrotus droebachiensis) and the frog (Xenopus laevis). These updated methods build on classical embryological approaches and enable robust, reproducible production of half-sized embryos. The resulting embryos are well suited for downstream applications, including in situ hybridization, morphogen gradient analysis, and high-throughput molecular profiling such as RNA sequencing and proteomics. Together, these protocols offer a powerful platform for investigating the genetic and physical principles that govern embryonic scaling across diverse deuterostome lineages.